Wisata Budaya Sebagai Penggerak Ekonomi Lokal di Kota Palembang - Ditto Arfin Al-Maraghi; Rahmawati Apia; M. Khairul Nawwari; Syawal Novaliansyah; Muhamad Rizky Putra Ramadhan; Taufik Romadhon (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Palembang City has emerged as a hub for culinary and cultural tourism, particularly through traditional cuisine and the production of songket and jumputan textiles, as part of efforts to stimulate local economic development. This study aims to examine the role of cultural tourism and traditional craftsmanship in supporting local economic growth and cultural sustainability. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, documentation, and questionnaires. Data analysis was conducted using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that cultural tourism and traditional textile industries generate positive economic impacts for local business actors, especially micro and small enterprises engaged in culinary and handicraft activities. In addition to economic benefits, cultural tourism contributes significantly to the preservation of local cultural values by encouraging active participation from artisans and entrepreneurs in maintaining the authenticity of traditional products. Overall, cultural tourism exhibits strong strategic potential as a dual mechanism for fostering local economic development and ensuring sustainable cultural preservation. These results provide important insights for policymakers in designing integrated tourism-based development strategies that balance economic growth with cultural conservation.